Faculty Mentoring Workshop - Julie Welch; Megan Palmer; Alice Mitchell; Darlene House; Kevin Rodgers; Lee Wilbur; Jeffrey Kline; Mary Ciccarelli; Daniel Rusyniak (Association of American Medical Colleges, 2014)
Abstract Introduction Mentoring is described in the literature as an essential component to career success, productivity, and satisfaction, yet many departments and institutions struggle to provide this transformative mentoring. Our Department of Emergency Medicine (EM) faced this very challenge. The results of a faculty needs assessment identified the "lack of mentorship" as one of the major barriers to both starting and finishing scholarly projects. These results highlighted the need for a more structured approach to faculty mentoring, however no standard existed within our department. Therefore, our department's Faculty Development Committee took on the challenge of creating opportunities for all faculty members to gain mentorship training and access. Methods This resource provides a strategy and materials for hosting a faculty mentoring workshop. The goals of the workshop are to introduce faculty to mentor-mentee concepts, provide a framework for building specific mentoring skills, and instill an enthusiasm for a collective mentoring community within your department. The skill building sessions include the topics of "Characteristics of Effective Mentors," "Maintaining the Mentoring Relationship," and "Generational Issues and Mentoring," to name a few. Additional tools include a mentoring self-assessment form and a workshop evaluation. Qualitative evaluation of the program is provided via postworkshop surveys of each session and the workshop overall. Results A total of 44 faculty and fellows attended the workshop and 29 (66%) completed the postworkshop evaluation survey, not including the faculty facilitators. The survey utilized a 5-point Likert Scale. Respondents agreed that all sessions were informative (average Likert scores ranged from 4.66 to 4.9), accomplished the stated objectives (4.76), were appropriate for EM faculty needs (4.66), including future junior faculty (4.69), provided information useful for academic development (4.62), and increased interest in mentoring (4.55). Discussion Possible revisions or adaptations of the workshop could be considered. The building block sessions could be adapted to include mentoring topics more relevant to the career paths of the faculty participants in teaching, research, or service. In addition, experienced facilitators can adapt the discussion of a particular session to the experience and skills of the participants. Finally, the workshop could be adapted for an audience of faculty, residents, fellows, or graduate students from other departments and institutions.